2018
DOI: 10.1111/jphp.12855
|View full text |Cite
|
Sign up to set email alerts
|

The role of melatonin on chemotherapy-induced reproductive toxicity

Abstract: Objectives Reproductive malfunctions after chemotherapy still are a reason of reducing fertility and need specialized intensive care. The aim of this review was to investigate the effect of melatonin on the reproductive system under threatening with chemotherapeutic drugs. Methods To find the role of melatonin in the reproductive system during chemotherapy, a full systematic literature search was carried out based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines in the electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 114 publications
0
50
0
2
Order By: Relevance
“…The proportion of PCNA-positive cells in the DM group increased in short- and long-term experiments. Anti-apoptosis is regarded as an essential function of melatonin in reproductive cells 31 . Melatonin could substantially reduce the number of apoptotic cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of PCNA-positive cells in the DM group increased in short- and long-term experiments. Anti-apoptosis is regarded as an essential function of melatonin in reproductive cells 31 . Melatonin could substantially reduce the number of apoptotic cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that continuous treatment with 2 mg/kg cisplatin leads to the activation of primordial follicles without causing apoptosis. [26][27][28][29][30] Thus, molecules suppressing the PI3K-p-AKT-mTORC1 pathway may prevent the loss of primordial follicles. One proposed molecule is melatonin (N-acetyl-5-methoxytryptamine, MT), a hormone produced and secreted by the pineal gland.…”
mentioning
confidence: 99%
“…Most of them confirmed the inhibition of tumor growth through different mechanisms, including apoptosis induction, cell cycle and epigenetics regulation, antioxidant activity, modulation of immunity and tumor microenvironment and regulation of angiogenesis [5]. MEL enhanced chemotherapy-induced toxicity in cancerous cells through increasing apoptosis, oxidative stress and mitochondrial malfunction also alleviated side-effects of chemotherapeutics, including reproductive injury [9,98,158,159,160]. An overcome of radioresistance after MEL administration was reported too [161].…”
Section: Mel and Cancer And Vice Versamentioning
confidence: 99%